Isolation and characterization of avian influenza viruses from raw poultry products illegally imported to Japan by international flight passengers. Issue 2 (16th October 2017) - Shibata, A.; Hiono, T.; Fukuhara, H.; Sumiyoshi, R.; Ohkawara, A.; Matsuno, K.; Okamatsu, M.; Osaka, H.; Sakoda, Y.
Summary: The transportation of poultry and related products for international trade contributes to transboundary pathogen spread and disease outbreaks worldwide. To prevent pathogen incursion through poultry products, many countries have regulations about animal health and poultry product quarantine. However, in Japan, animal products have been illegally introduced into the country in baggage and confiscated at the airport. Lately, the number of illegally imported poultry and the incursion risk of transboundary pathogens through poultry products have been increasing. In this study, we isolated avian influenza viruses (AIVs) from raw poultry products illegally imported to Japan by international passengers. Highly (H5N1 and H5N6) and low (H9N2 and H1N2) pathogenic AIVs were isolated from raw chicken and duck products carried by flight passengers. H5 and H9 isolates were phylogenetically closely related to viruses isolated from poultry in China, and haemagglutinin genes of H5N1 and H5N6 isolates belonged to clades 2.3.2.1c and 2.3.4.4, respectively. Experimental infections of H5 and H9 isolates in chickens and ducks demonstrated pathogenicity and tissue tropism to skeletal muscles. To prevent virus incursion by poultry products, it is important to encourage the phased cleaning based on the disease control and eradication and promote the reduction in contamination risk in animal products.